2017
DOI: 10.3390/ijms18081632
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Role of ASCT2 (SLC1A5) in KRAS-Mutated Colorectal Cancer

Abstract: Mutation in the KRAS gene induces prominent metabolic changes. We have recently reported that KRAS mutations in colorectal cancer (CRC) cause alterations in amino acid metabolism. However, it remains to be investigated which amino acid transporter can be regulated by mutated KRAS in CRC. Here, we performed a screening of amino acid transporters using quantitative reverse-transcription polymerase chain reaction (RT-PCR) and then identified that ASCT2 (SLC1A5) was up-regulated through KRAS signaling. Next, immun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
56
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 63 publications
(56 citation statements)
references
References 33 publications
0
56
0
Order By: Relevance
“…Similar to the situation in MYC-driven cancer cells, glutamine uptake is enhanced in K-Ras-driven cells via upregulation of SLC1A5 181 . Additionally, K-Ras-driven cells are characterized by increased expression of GOT1 and GOT2 182,183 .…”
Section: Crosstalk Between Glutamine Metabolism and Oncogenic Signalingmentioning
confidence: 67%
“…Similar to the situation in MYC-driven cancer cells, glutamine uptake is enhanced in K-Ras-driven cells via upregulation of SLC1A5 181 . Additionally, K-Ras-driven cells are characterized by increased expression of GOT1 and GOT2 182,183 .…”
Section: Crosstalk Between Glutamine Metabolism and Oncogenic Signalingmentioning
confidence: 67%
“…3A). Indeed, previous immunohistochemistry (IHC) studies found that both SLC1A5 and SLC7A5 were up-regulated in colon cancer cells (Huang et al 2014;Wang et al 2016;Toda et al 2017).…”
Section: Myc Promotes the Expression Of Trp Transporters And Enzymes mentioning
confidence: 99%
“…9,37,38 Furthermore, glutamine is the major carbon source for the tricarboxylic acid cycle when RAS is activated. 38 SLC1A5 is upregulated through KRAS signaling in colorectal cancer, 39 and the conversion of glutamine to glutamate by GLS is modulated by RAS. 38 This is in agreement with our findings that KRAS mutated tumors show a trend toward a higher SLC1A5 mRNA expression and a significantly higher GLS mRNA expression.…”
Section: Nsclc Tumor Cell Metabolism In Relation To Histological Subtmentioning
confidence: 99%